Beyond Conspiracy: 25 Years after the Aquino Assassination - Tanyag, Maria Fleurdelis R. (Kasarinlan: Philippine Journal of Third World Studies; Vol 23 No 1 (2008): Contentious Politics, 2008)
Review of the documentary Beyond Conspiracy: 25 Years after the Aquino Assassination
Keywords: Benigno Aquino; Ninoy; assassination